2018
DOI: 10.1016/j.fuel.2018.03.181
|View full text |Cite
|
Sign up to set email alerts
|

Method for determination of flammability limits of gaseous compounds diluted with N2 and CO2 in air

Abstract: The present work studies the flammability limits of combustible-diluent-air mixtures at 25°C and 1 atm pressure. The diluent species, considered in this study, were nitrogen and carbon dioxide. A factor called k FL was obtained from mass and energy conservation, this factor relates the flammability limit of a combustible-air mixture to that of a combustible-diluent-air mixture. The factor k FL varies with diluent concentration. Nevertheless, it was shown that an average value of this factor k () FL av can repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
(102 reference statements)
0
16
0
1
Order By: Relevance
“…Segmentation information for determining the value of B attribute for the T set is computed using (6).…”
Section: Decision Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Segmentation information for determining the value of B attribute for the T set is computed using (6).…”
Section: Decision Treesmentioning
confidence: 99%
“…Although chemicals play an important role in the daily life of people around the world [5,6], some of the work accidents occur due to the chemicals. The chemical industry produces * Corresponding Author a wide variety of substances necessary for daily use and chemical hazards generally arise from chemical synthesis or production, processing, transportation and misuse.…”
Section: Introductionmentioning
confidence: 99%
“…Feng B et al 7 found the gas disturbances decreased the LFL of the propane−air mixture. Mendiburu et al 8 investigated the changes of the flammability limits of propane and other hydrocarbons diluted by CO 2 in air atmosphere. Results show that the LFL of the gas mixture increased with increasing CO 2 concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Modern technologies are impossible without the use of explosive substances. Fuel-air mixtures (FA), fuel and lubricants (fuels and lubricants), flammable liquids (flammable liquids) are used in all areas of society, both in industry and in everyday life [1,2]. One of the main tasks of society is to ensure the safety of the population and territories from emergency situations (ES) of natural and man-made characters [3].…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of studies of explosions of fuel-air mixtures is due to the significant risk of accidents associated with them and the need to predict the extent of possible dangerous consequences when designing hazardous production facilities and developing additional safety measures [1,6,7,8]. When considering the processes of explosive transformations of fuel assemblies, special attention is paid to possible modes of combustion of an explosive cloud and consideration of factors determining the conditions for the onset of detonation or deflagration with a corresponding speed of flame front propagation [9].…”
Section: Introductionmentioning
confidence: 99%